(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine, how the Application of Electronic Parking Terminal System Innovations Seen From the Innovation Attributes. This research used a qualitative descriptive method, which was to provide an overview or explanation of the application of the innovative electronic parking terminal system (TPE) in the city of Makassar, with a total of 6 informants. Data collection techniques used observation, interviews and documentation. While data analysis used data reduction, data presentation and drawing conclusions. The results of this study showed that PD. Parkir Makassar Raya had implemented the Parking Terminal System (TPE) program in Makassar City but it had not been maximized. This was due to the fact that there were still people who disagree and the lack of socialization counducted regarding the Electronic Parking Terminal System (TPE) to the public.